Penerapan Metode Drill untuk Meningkatkan Jiwa Kewirausahaan dan Hasil Belajar Matematika pada Siswa Kelas III di SD Inpres Tangkala I Kota Makassar - Safira, Dian; Afni, Nur; Erwin Nurdiansyah (AIJER: Algazali International Journal Of Educational Research, 2025)
Abstrak: This study aims to describe the implementation of the drill method to enhance students’ entrepreneurial spirit and mathematics learning outcomes. This research employed a classroom action research (CAR) approach conducted in two eyeles, with each cycle consisting of planning implementation, observation, and reflection. The subjects were 17 third-grade students of SD Inpres Tangkala I, Makassar City. Data were collected through tests, observations, and assessment sheets, and analyzed both qualitatively and quantitatively using descriptive statistics. The results indicated that the application of a drill method, combined with an entrepreneurial approuach through a market day project, improved students’ learning outcomes. The average student score increased from 42.05 in the pre-actionstage to 72.94 in Cycle I, and further improved to 83.23 in Cycle II. This improvement demonstrates that the drill method is effective in enhancing students’ understanding of mathematical concepts and in developing entrepreneurial character trats such as creativity, courage, and independence in learning. With 88% of students achieving scores above the minimum mastery criteria, it can be concluded that this study successfully improved both student learning outcomes and entrepreneurial spirits.